Method for preparing battery-grade lithium carbonate by using salt lake crude lithium sulfate

By using a method of additive roasting-dissolution filtration-calcium and magnesium removal-lithium precipitation, battery-grade lithium carbonate is directly prepared from crude lithium sulfate in salt lakes using lanthanide metal compound porous carbon powder and calcium-magnesium chelate resin. This method solves the problems of long process flow and high cost, and achieves efficient and low-cost lithium recovery and impurity removal.

CN120887442APending Publication Date: 2025-11-04LONGNAN JINTAIGE COBALT IND CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202511057680.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-30
Publication Date
2025-11-04

AI Technical Summary

Technical Problem

Existing technologies cannot directly convert crude lithium sulfate from salt lakes into battery-grade lithium carbonate. The process is lengthy and costly, especially the boron removal process, which requires expensive resins.

Method used

A method of additive roasting-dissolution filtration-calcium and magnesium removal-lithium precipitation was adopted, which utilizes porous carbon powder loaded with lanthanide metal compounds for adsorption and reaction, combined with calcium and magnesium chelating resin for deep removal of impurities, to directly prepare battery-grade lithium carbonate.

Benefits of technology

The process flow was shortened, costs were reduced, and the overall lithium recovery rate was improved. Furthermore, by loading lanthanum carbonate or lanthanum hydroxide, the effect of solid chlorine removal was achieved, reducing the risk of equipment corrosion.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN120887442A_ABST
    Figure CN120887442A_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing battery-grade lithium carbonate by using salt lake crude lithium sulfate. The method comprises the following steps: roasting salt lake crude lithium sulfate powder through an auxiliary agent, dissolving with water, filtering to obtain a primary purified solution, removing calcium and magnesium to obtain a secondary purified solution, and finally preparing the battery-grade lithium carbonate from the salt lake crude lithium sulfate through a lithium precipitation reaction. According to the method, boron removal ion exchange resin does not need to be used for removing the boron element, the boron removal rate is high, chlorine can be fixed and removed while boron is removed, material hardening is reduced, material input is saved, the technological process is shortened, and the production cost can be reduced.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present application relates to the technical field of salt lake resource utilization, and particularly to a method for preparing battery-grade lithium carbonate from crude lithium sulfate of a salt lake. BACKGROUND

[0002] The crude lithium sulfate of a salt lake usually contains Na (sodium), Mg (magnesium), Ca (calcium), K (potassium), Cl (chlorine) and B (boron) and other impurities. The current processing technology mainly adopts steps such as resin boron removal, magnesium precipitation and calcium precipitation, to prepare industrial-grade lithium carbonate, and then secondary purification is performed through carbonization and cracking to achieve the standard of battery-grade lithium carbonate. However, this process flow is long, and battery-grade lithium carbonate cannot be directly prepared in one step. In addition, the boron removal process needs to use expensive boron removal resin, which further increases the cost. Therefore, developing a new method capable of directly converting the crude lithium sulfate of a salt lake into battery-grade lithium carbonate has important significance for reducing the cost and shortening the process flow. SUMMARY

[0003] In view of the deficiencies of the prior art, the present application provides a method for preparing battery-grade lithium carbonate from crude lithium sulfate of a salt lake. The method of the present application is to prepare battery-grade lithium carbonate from the crude lithium sulfate of a salt lake by the way of auxiliary agent calcination-dissolution filtration-calcium and magnesium removal-lithium precipitation. This scheme does not need to use boron removal ion exchange resin, and at the same time reduces the multi-stage extraction process, saves the material input, shortens the process flow, and can reduce the production cost.

[0004] The technical scheme of the present application is as follows:

[0005] A method for preparing battery-grade lithium carbonate from crude lithium sulfate of a salt lake, the method comprising the following steps:

[0006] (1) porous carbon is added to a lanthanum chloride solution containing a surfactant under reduced pressure to perform an adsorption reaction, and then the porous carbon after adsorption is stirred in ammonia gas or a mixture of ammonia gas and carbon dioxide, and then washed and dried or directly dried to obtain porous carbon powder loaded with lanthanide metal compounds;

[0007] (2) the crude lithium sulfate powder of a salt lake is mixed with the porous carbon powder loaded with lanthanide metal compounds, and high-temperature sintering is performed under the protection of nitrogen or inert gas, and then water dissolution, filtration and washing of the filter residue are performed to obtain a first-purified lithium sulfate solution;

[0008] (3) sodium carbonate is added to the first-purified lithium sulfate solution, and then the pH of the solution is adjusted with sodium hydroxide to convert calcium and magnesium ions into precipitates, the filtrate is collected by filtration, calcium and magnesium are further removed by a calcium and magnesium chelating resin, and then filtration is performed to obtain a second-purified solution;

[0009] (4) adding sodium carbonate solution to the secondary purification liquid to perform a lithium precipitation reaction, and after the reaction is completed, centrifugation, washing, drying, airflow crushing and magnetic removal are performed to obtain the battery-grade lithium carbonate.

[0010] Further, in step (1), the particle size of the porous carbon powder ranges from <25 μm, the effective pore size is <100 nm, and the specific surface area is 600-1200 m 2 / g; the concentration of the lanthanum chloride solution is 2.5-3.0 mol / L; the surfactant is selected from any one of CTAB, polyethylene glycol, PVP, sodium dodecyl sulfate and sodium dodecyl benzene sulfonate; the addition amount of the surfactant is 0.5-2% of the mass of the lanthanum chloride solution; and the mass / volume ratio of the porous carbon to the lanthanum chloride solution is 1:0.5-0.6 kg / L.

[0011] Further, in step (1), the adsorption temperature is room temperature, and the time is 20-40 min; when the porous carbon is placed in a mixed gas of ammonia and carbon dioxide, the volume ratio of ammonia to carbon dioxide is 2:1; the stirring reaction temperature is room temperature, and the time is 10-20 h; and the drying temperature is 100-150 ℃, and the time is 4-6 h.

[0012] Further, in step (1), the lanthanum series metal compound includes at least one of lanthanum carbonate and lanthanum hydroxide; and the lanthanum series metal compound in the porous carbon powder is loaded in the pore structure of the porous carbon, and the loading amount is 20-30 wt%.

[0013] Further, in step (2), the mass ratio of the salt lake crude lithium sulfate powder to the porous carbon powder is 5:2-3.

[0014] Further, in step (2), the high-temperature sintering temperature is 600-700 ℃, and the time is 1-3 h.

[0015] Further, in step (3), the molar amount of the sodium carbonate is 1.1-1.2 times the molar amount of Ca 2+ in the primary lithium sulfate purification liquid; and the pH of the sodium hydroxide adjusting solution is 11.5-12.0.

[0016] Further, in step (3), the residence time of the filtrate in the calcium-magnesium chelating resin is 10-30 min.

[0017] Further, in step (4), the ratio of the molar amount of the sodium carbonate to the molar amount of Li + in the secondary purification liquid is 1.05-1.1:2.

[0018] Further, in step (4), the lithium precipitation reaction temperature is 90-95 ℃, and the time is 1.5-2 h.

[0019] The beneficial technical effects of the present application are as follows:

[0020] The present application prepares crude lithium sulfate from salt lake containing Na, Mg, Ca, K, Cl, B into battery-grade lithium carbonate by roasting-dissolving-filtration-calcium and magnesium removal-lithium precipitation method with the aid of the agent (porous carbon powder loaded with lanthanide metal compound).

[0021] In the roasting process, the conversion behavior of boric acid or boric acid salt (such as Na2B4O7) impurities in the material at high temperature is as follows:

[0022] H3BO3→HBO2(boronic acid) + H2O↑

[0023] 4HBO2→2B2O3(oxidized boron) + 2H2O↑

[0024] Na2B4O7+ Ca 2+ →CaB4O7+2Na +

[0025] Roasting can convert boron into insoluble oxide (B2O3) or combine with metal oxides (such as CaO, MgO) to form calcium / magnesium borate. According to the experimental results, 20% of the calcium is combined into calcium borate, and the formation of magnesium borate is less, and most of the Mg enters the solution. Roasting can convert boron impurities into insoluble substances in one step, and then remove boron impurities by dissolving and filtering, which has the advantages of short process, low cost and high efficiency.

[0026] However, in the sintering process, XCl·H2O (X mainly Li) in the material decomposes to produce HCl, which can cause serious corrosion to the equipment, making it difficult to produce industrially. Therefore, the present application adds loose porous carbon powder loaded with nanoscale lanthanum carbonate or lanthanum hydroxide during sintering. The porous carbon material can capture the HCl gas produced by decomposition, and then the nanoscale lanthanum carbonate or lanthanum hydroxide loaded in the porous carbon reacts with HCl at high temperature to form LaOCl. Since LaOCl is insoluble, it can also be separated by dissolving and filtering. The addition of porous carbon composite lanthanum carbonate or lanthanum hydroxide aid has the dual effect of fixing and removing chlorine, and at the same time, the porous carbon powder can also alleviate the hardening of the material during sintering, which is beneficial to industrial production operation. It is worth noting that the aid can be effectively recycled and recycled, with low use cost.

[0027] After dissolving and filtering, the lithium sulfate solution can be precipitated into battery-grade lithium carbonate in one step after adjusting the ph and removing impurities by resin adsorption. K + , Na + ions in the lithium-containing mother liquor can be further recovered as by-products, and residual Li +The ions are returned to the lithium sulfate solution of the first purification, and the lithium precipitation recovery is continuously carried out, so that the battery-grade lithium carbonate can be prepared while the high lithium comprehensive recovery rate is maintained. BRIEF DESCRIPTION OF DRAWINGS

[0028] Figure 1 The process flow chart of the present application is shown. DETAILED DESCRIPTION

[0029] The present application will be described in detail below in combination with the drawings and examples.

[0030] The particle size of the porous carbon used in the present application is <25 μm, the effective pore size is <100 nm, the specific surface area is 600-1200 m 2 / g, and it is purchased from Shanghai Aldrin Biochemical Technology Co., Ltd. with the product code C112241. The purchased porous carbon is ground and sieved with a 500-mesh ultrasonic sieve, and the undersize is used in the subsequent examples.

[0031] The porous carbon@lanthanum hydroxide powder and the porous carbon@lanthanum carbonate powder in the following examples of the present application can be recovered. The specific recovery method is as follows: the filter residue after washing and filtering of the sample after high-temperature sintering in step (2) of the example is recovered, dissolved with hydrochloric acid, and then filtered and washed to obtain a porous carbon powder and a lanthanum chloride filtrate. The filtrate is concentrated under reduced pressure to a concentration of 2.5-3.0 mol / L. The porous carbon is added to the concentrated solution containing a surfactant under normal temperature and reduced pressure, and the adsorption reaction is carried out for 20-40 min. Then, the adsorbed porous carbon is placed in an ammonia gas or a mixed gas of ammonia gas and carbon dioxide under normal temperature and stirred for 10-20 h. Then, it is dried at 100-150 °C for 4-6 h to obtain a porous carbon powder loaded with a lanthanum series metal compound. When the porous carbon is placed in the mixed gas of ammonia gas and carbon dioxide, the volume ratio of ammonia gas to carbon dioxide is 2:1. The surfactant is selected from any one of CTAB, polyethylene glycol, PVP, sodium dodecyl sulfate, and sodium dodecyl benzene sulfonate. The addition amount of the surfactant is 0.5-2% of the mass of the lanthanum chloride solution.

[0032] Example 1

[0033] A method for preparing battery-grade lithium carbonate from crude lithium sulfate of a salt lake, the flow chart is shown as follows, comprising the following steps: Figure 1

[0034] (1) 10 kg of porous carbon is added to 5.0 L of a lanthanum chloride solution containing 0.2 wt% of sodium dodecyl benzene sulfonate under reduced pressure, and the concentration is 3.0 mol / L. The adsorption is carried out at room temperature for 30 min, and then it is placed in an ammonia gas environment and stirred at room temperature for 12 h, so that La 3+ ​The lanthanum hydroxide is co-precipitated in the pores of the porous carbon, and then dried at 120°C for 6h to obtain the porous carbon powder loaded with 22wt% of lanthanum hydroxide (porous carbon@lanthanum hydroxide powder).

[0035] (2) The crude lithium sulfate powder from salt lake and the porous carbon@lanthanum hydroxide powder are mixed in a mass ratio of 5:2, and high-temperature sintering is performed by heat treatment at 600°C for 2h under a nitrogen atmosphere. Then, the sample is dissolved in water, the filtrate is collected by pressure filtration, the filter residue is washed and filtered again, and the filtrate is collected. The first-purified lithium sulfate solution (first-purified solution) is obtained by combining the filtrates. As can be seen from the element content results in Table 1, the boron and chlorine impurities have been removed.

[0036] (3) 10.00L of the first-purified solution is taken, 10.2g of sodium carbonate powder is added, and after stirring and reaction, liquid alkali is added to adjust the pH to 11.6, so that the calcium and magnesium ions are converted into precipitates. The filtrate is collected by filtration, and the filtrate is passed into a calcium-magnesium chelating resin to remove calcium and magnesium by adsorption, with a residence time of 20min. The second-purified lithium sulfate solution (second-purified solution) is obtained by filtration. As can be seen from the element content results in Table 1, the calcium and magnesium impurities have been removed.

[0037] (4) The second-purified solution obtained in step (3) is heated to 90°C, and 92°C, 4.91L of a 300g / L sodium carbonate solution is added to perform lithium precipitation reaction for 1.5h. Then, the precipitate and the lithium precipitation mother liquor are collected by filtration. After washing, drying, airflow crushing and demagnetization, the battery-grade lithium carbonate is obtained.

[0038] The lithium precipitation mother liquor is treated with sodium sulfate acidification, evaporated, and then evaporated and crystallized to obtain potassium-containing sodium sulfate and a remaining liquid. After freeze crystallization of the remaining liquid, sodium sulfate and a mother liquor (the mother liquor is returned to the first-purified solution for continued lithium precipitation recovery) are obtained.

[0039] Table 1

[0040] Element Li Ca Mg Na K B Cl Crude lithium sulfate (%) 9.56 0.22 1.27 0.52 0.98 0.51 1.02 Primary purification liquor (g / L) 18.53 0.35 2.72 1.23 2.17 0.001 0.003 Secondary purification liquor (g / L) 18.42 0.002 0.003 1.37 2.07 0.000 0.003

[0041] Example 2

[0042] A method for preparing battery-grade lithium carbonate from crude lithium sulfate from salt lake, as shown in the flowchart Figure 1 , comprises the following steps:

[0043] (1) 10kg of porous carbon is added to 5.5L of a lanthanum chloride solution containing 1wt% of polyethylene glycol with a concentration of 2.7mol / L under reduced pressure, and adsorption reaction is performed at room temperature for 20min. Then, the sample is placed in an environment of mixed gas of ammonia and carbon dioxide (V NH3 :V CO2 =2:1) and stirred at room temperature for 18h to convert La 3+The lanthanum carbonate was co-precipitated in the pores of the porous carbon, then washed with water and dried at 150°C for 4h to obtain the porous carbon powder loaded with 25wt% of lanthanum carbonate (porous carbon@lanthanum carbonate powder).

[0044] (2) The salt lake crude lithium sulfate powder was mixed with the porous carbon@lanthanum carbonate powder at a mass ratio of 5:2.5, high-temperature sintering was carried out by heat treatment at 700°C for 1h under a nitrogen atmosphere, then the sample was dissolved in water, the filtrate was collected by pressure filtration, the filter residue was washed and filtered again to collect the filtrate, and the filtrates were combined to obtain a primary purified lithium sulfate solution (primary purified solution), as can be seen from the element content results in Table 2, the boron and chlorine impurities have been removed.

[0045] (3) 20L of the primary purified solution was taken, 22.5g of sodium carbonate powder was added, after stirring and reaction, liquid alkali was added to adjust the pH to 12.0, the calcium and magnesium ions were converted into precipitates, the filtrate was collected by filtration, and the filtrate was passed into the calcium and magnesium chelating resin to remove calcium and magnesium by adsorption, the residence time was maintained at 30min, and then filtration was carried out to obtain a secondary lithium sulfate solution (secondary purified solution), as can be seen from the element content results in Table 2, the calcium and magnesium impurities have been removed.

[0046] (4) The secondary purified solution obtained in step (3) was heated to 95°C, and a 10.35L solution of 300g / L sodium carbonate at 95°C was added to carry out lithium precipitation reaction for 2.0h, then the precipitate and the lithium precipitation mother liquor were collected by filtration, the precipitate was washed, dried, air-pulverized and demagnetized to obtain the battery-grade lithium carbonate.

[0047] The lithium precipitation mother liquor was treated with sodium sulfate acidification, evaporated, and then evaporated and crystallized to obtain potassium-containing sodium sulfate and a remaining liquid, and the remaining liquid was subjected to freeze crystallization to obtain sodium sulfate and a mother liquor (the mother liquor was returned to the primary purified solution for continued use in lithium precipitation recovery).

[0048] Table 2

[0049]

[0050]

[0051] Example 3

[0052] A method for preparing battery-grade lithium carbonate from salt lake crude lithium sulfate, the flow chart is as shown in Figure 1 , which comprises the following steps:

[0053] (1) 10kg of porous carbon was added to 6.0L of a lanthanum chloride solution containing 1.2wt% PVP at a concentration of 2.5mol / L under reduced pressure, adsorption was carried out at room temperature for 20min, then it was placed in an ammonia environment and stirred at room temperature for 15h to convert La 3+The lanthanum hydroxide was co-precipitated in the pores of the porous carbon, and then dried at 130°C for 5h to obtain the porous carbon powder loaded with 23wt% of lanthanum hydroxide (porous carbon@lanthanum hydroxide powder).

[0054] (2) The crude lithium sulfate powder from the salt lake was mixed with the porous carbon@lanthanum hydroxide powder at a mass ratio of 5:3, and high-temperature sintering was performed by heat treatment at 650°C for 2h under a nitrogen atmosphere. Then, the sample was dissolved in water, the filtrate was collected by pressure filtration, the filter residue was washed and filtered again, and the filtrate was collected. The first-purified lithium sulfate solution (first-purified solution) was obtained by combining the filtrates. As can be seen from the element content results in Table 3, the boron and chlorine impurities have been removed.

[0055] (3) 15L of the first-purified solution was taken, 10.2g of sodium carbonate powder was added, and after stirring and reaction, liquid alkali was added to adjust the pH to 11.6, so that the calcium and magnesium ions were converted into precipitates. The filtrate was collected by filtration, and the calcium and magnesium were removed by adsorption into a calcium-magnesium chelating resin with a residence time of 10min. The second-purified lithium sulfate solution (second-purified solution) was obtained by filtration. As can be seen from the element content results in Table 1, the calcium and magnesium impurities have been removed.

[0056] (4) The second-purified solution obtained in step (3) was heated to 92°C, and 7.80L of a 300g / L sodium carbonate solution at 90°C was added to perform lithium precipitation reaction for 1.5h. Then, the precipitate and the lithium precipitation mother liquor were collected by filtration. After washing, drying, airflow crushing and demagnetization, the battery-grade lithium carbonate was obtained.

[0057] After the lithium precipitation mother liquor was acidified with sodium sulfate and evaporated, sodium sulfate containing potassium and residual liquid were obtained by evaporation crystallization. Sodium sulfate and mother liquor (returned to the first-purified solution for continued lithium precipitation recovery) were obtained by freeze crystallization of the residual liquid.

[0058] Table 3

[0059]

[0060]

[0061] Comparative Example 1

[0062] The method of Comparative Example 1 is basically the same as that of Example 1, except that the temperature of high-temperature sintering in step (1) of the comparative example is 450°C. The element content of each purified solution in the comparative example is shown in Table 4.

[0063] Table 4

[0064] Element Li Ca Mg Na K B Cl Crude lithium sulfate (%) 9.56 0.22 1.27 0.52 0.98 0.51 1.02 Primary purification liquor (g / L) 18.62 0.42 2.68 1.18 2.08 0.95 0.88 Secondary purification liquor (g / L) 18.43 0.003 0.003 1.21 2.00 0.42 0.87

[0065] As can be seen from the results in Table 4, at a lower sintering temperature, boron impurities cannot be completely converted into insoluble substances such as boron oxide, and chlorine impurities cannot react with lanthanum hydroxide or lanthanum carbonate to form LaOCl, resulting in poor boron removal and chlorine removal effects. The presence of boron impurities prevents the one-step precipitation of battery-grade lithium carbonate, and chlorine impurities are enriched in the tail-end sodium sulfate by-product, affecting the quality of the by-product.

[0066] Comparative Example 2

[0067] The method of Comparative Example 2 is basically the same as that of Example 1, except that in step (1) of the present comparative example, the volume ratio of crude lithium sulfate powder from salt lake to porous carbon@lanthanum hydroxide powder is 10:1. The elemental content of the purified liquid at each stage of the present comparative example is shown in Table 5.

[0068] Table 5

[0069] Element Li Ca Mg Na K B Cl Crude lithium sulfate (%) 9.56 0.22 1.27 0.52 0.98 0.51 1.02 Primary purification liquor (g / L) 18.87 0.31 2.63 1.24 2.04 0.002 0.21 Secondary purification liquor (g / L) 18.78 0.002 0.002 1.26 1.98 0.001 0.20

[0070] As can be seen from the results in Table 5, too little addition of porous carbon@lanthanum hydroxide powder results in poor chlorine removal and solidification effects, which can easily cause equipment corrosion and affect the quality of the end sodium sulfate by-product.

[0071] The above description is only a preferred embodiment of the present application, and the present application is not limited to the above examples. It can be understood that other improvements and changes directly derived or thought of by those skilled in the art without departing from the spirit and concept of the present application should be considered to be within the scope of protection of the present application.

Claims

1. A method for preparing battery-grade lithium carbonate from crude lithium sulfate produced from salt lakes, characterized in that, The method includes the following steps: (1) Porous carbon is added to a lanthanum chloride solution containing surfactant under reduced pressure to carry out an adsorption reaction. The adsorbed porous carbon is then placed in ammonia or a mixture of ammonia and carbon dioxide and stirred to react. After washing and drying or direct drying, porous carbon powder loaded with lanthanide metal compounds is obtained. (2) The crude lithium sulfate powder from the salt lake is mixed with porous carbon powder loaded with lanthanide metal compounds, and sintered at high temperature under nitrogen or inert gas protection. Then, the mixture is dissolved in water, filtered, and the filter residue is washed to obtain a first-grade purified lithium sulfate solution. (3) Add sodium carbonate to the primary lithium sulfate purification solution, then adjust the pH of the solution with sodium hydroxide to convert calcium and magnesium ions into precipitates, filter and collect the filtrate, then pass it through calcium and magnesium chelating resin to remove calcium and magnesium, and then filter to obtain the secondary purification solution. (4) Add sodium carbonate solution to the secondary purified solution to carry out lithium precipitation reaction. After the reaction is completed, the battery-grade lithium carbonate is obtained by centrifugation, washing, drying, air jet pulverization and demagnetization.

2. The method according to claim 1, characterized in that, In step (1), the porous carbon powder has a particle size range of <25μm, an effective pore size of <100nm, and a specific surface area of ​​600~1200m². 2 / g; the concentration of the lanthanum chloride solution is 2.5-3.0 mol / L; the surfactant is selected from any one of CTAB, polyethylene glycol, PVP, sodium dodecyl sulfate, and sodium dodecylbenzene sulfonate; the amount of surfactant added is 0.5-2% of the mass of the lanthanum chloride solution; the mass-volume ratio of the porous carbon to the lanthanum chloride solution is 1:0.5-0.6 kg / L.

3. The method according to claim 1, characterized in that, In step (1), the adsorption temperature is room temperature and the time is 20-40 min; when the porous carbon is placed in a mixture of ammonia and carbon dioxide, the volume ratio of ammonia to carbon dioxide is 2:1; the stirring reaction temperature is room temperature and the time is 10-20 h; the drying temperature is 100-150℃ and the time is 4-6 h.

4. The method according to claim 1, characterized in that, In step (1), the lanthanide metal compound includes at least one of lanthanum carbonate and lanthanum hydroxide; the lanthanide metal compound in the porous carbon powder is loaded in the pore structure of the porous carbon, and the loading amount is 20-30 wt%.

5. The method according to claim 1, characterized in that, In step (2), the mass ratio of the crude lithium sulfate powder from the salt lake to the porous carbon powder is 5:2 to 3.

6. The method according to claim 1, characterized in that, In step (2), the high-temperature sintering temperature is 600-700℃ and the time is 1-3h.

7. The method according to claim 1, characterized in that, In step (3), the molar amount of sodium carbonate is equal to the amount of Ca in the primary lithium sulfate purification solution. 2+ The amount of sodium hydroxide is 1.1 to 1.2 times the molar amount; the pH of the sodium hydroxide solution is adjusted to 11.5 to 12.

0.

8. The method according to claim 1, characterized in that, In step (3), the residence time of the filtrate in the calcium-magnesium chelating resin is 10 to 30 minutes.

9. The method according to claim 1, characterized in that, In step (4), the molar amount of sodium carbonate is related to the amount of Li in the secondary purification solution. + The molar ratio is 1.05 to 1.1:

2.

10. The method according to claim 1, characterized in that, In step (4), the temperature of the lithium precipitation reaction is 90-95°C and the time is 1.5-2 hours.